Mesophyll conductance to CO2 and Rubisco as targets for improving intrinsic water use efficiency in C3 plants. (11th December 2015) - Flexas, J.; Díaz‐Espejo, A.; Conesa, M. A.; Coopman, R. E.; Douthe, C.; Gago, J.; Gallé, A.; Galmés, J.; Medrano, H.; Ribas‐Carbo, M.; Tomàs, M.; Niinemets, Ü.
Abstract: Water limitation is a major global constraint for plant productivity that is likely to be exacerbated by climate change. Hence, improving plant water use efficiency (WUE) has become a major goal for the near future. At the leaf level, WUE is the ratio between photosynthesis and transpiration. Maintaining high photosynthesis under water stress, while improving WUE requires either increasing mesophyll conductance ( gm ) and/or improving the biochemical capacity for CO2 assimilation—in which Rubisco properties play a key role, especially in C3 plants at current atmospheric CO2 . The goals of the present analysis are: (1) to summarize the evidence that improving gm and/or Rubisco can result in increased WUE; (2) to review the degree of success of early attempts to genetically manipulate gm or Rubisco; (3) to analyse how gm, gsw and the Rubisco's maximum velocity ( Vcmax ) co‐vary across different plant species in well‐watered and drought‐stressed conditions; (4) to examine how these variations cause differences in WUE and what is the overall extent of variation in individual determinants of WUE; and finally, (5) to use simulation analysis to provide a theoretical framework for the possible control of WUE by gm and Rubisco catalytic constants vis‐à‐vis gsw under water limitations. Abstract : In this review, we use a meta‐analysis of a novel large literature data set, to assess how stomatal and mesophyll conductance to CO2 and Rubisco characteristics are interrelated across plants in nature, providing a precise biotechnological perspective for achieving the urgent goal of improving leaf intrinsic water use efficiency (WUE) while maintaining or increasing net CO2 assimilation.